2015
DOI: 10.1080/19440049.2015.1049218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interactions between tea (Camellia sinensis) extracts and ascorbic acid on their antioxidant activity: analysis with interaction indexes and isobolograms

Abstract: Products containing natural additives, including antioxidants, are usually perceived by consumers as safer than those with synthetic ones. Natural antioxidants, besides having a preservative activity, may exert beneficial health effects. Interactions between antioxidants may significantly change their antioxidant activity, thus in designing functional foods or food/cosmetic ingredients knowledge about the type of interactions could be useful. In the present study, the interactions between ascorbic acid (AA; vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…Theaflavins, a type of phenolic compound in black tea, may contribute to strong antioxidant properties that affect the DPPH scavenging activity and total phenols [23,[29][30][31][32]. However, the therapeutic activities of black tea are attributed not only to the antioxidant activity of its components but also to the ability of bioactive molecules to interact with several biological targets [33,34]. At a high temperature, chemical degradation can occur, changing the structure of temperature-sensitive molecules such as (-)-epigallocatechin-3-gallate.…”
Section: Effect Of Infusion Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Theaflavins, a type of phenolic compound in black tea, may contribute to strong antioxidant properties that affect the DPPH scavenging activity and total phenols [23,[29][30][31][32]. However, the therapeutic activities of black tea are attributed not only to the antioxidant activity of its components but also to the ability of bioactive molecules to interact with several biological targets [33,34]. At a high temperature, chemical degradation can occur, changing the structure of temperature-sensitive molecules such as (-)-epigallocatechin-3-gallate.…”
Section: Effect Of Infusion Temperaturementioning
confidence: 99%
“…Wide variations are noted among different kinds of black tea in terms of DPPH scavenging ability [9,22,[34][35][36][37][38] and total phenolic content [6,20,32,36,39]; these are highly dependent on the genetic background and growing conditions (such as temperature, nitrogen availability, and light conditions) of the plant material. The IC 50 of black tea in this study was 28.4 ± 4.8 µg/mL, and it falls within the range of 12.7-118.7 µg/mL found by other authors [34,38]. The total phenolic content in this study was 178.6 ± 16.4 mg GAE/g dry leaf, and it was in the range from 50.9 ± 4.1 mg GAE/g dry leaf [32] to 274.3 ± 0.0 mg GAE/g dry leaf [20].…”
Section: Effect Of Storage Time and Storage Temperaturementioning
confidence: 99%
“…Lower [36], higher [15] or similar [38] value have been reported. On the other hand, there is well known that polyphenols as well as other bioactive compounds could interact between each other, which is clearly visible in the antioxidant activities of their mixtures [3,8,11,20]. Mouly et al [17] reported that over 300 remedies and mineral supplements are capable of interacting with food components through essential mineral antagonism, induction of inhibition of micronutrient metabolism.…”
Section: Antioxidant Activity Of Selenium Compounds In the Mixtures Wmentioning
confidence: 99%
“…The antioxidant capacity of fulvic acid products was determined using the TEAC method with ABTS •+ radical cation as described by Re et al [25]. Moreover, the FRAP assay was carried out by the method of Benzie and Strain [26] with modifications previously described [27].…”
Section: Determination Of the Antioxidant Capacitymentioning
confidence: 99%
“…A volume of 0.008 mL of sample was added to 0.792 mL of the 10 mM ferric-TPTZ reagent and the increase in absorbance at 593 nm was measured after 8 min. The FRAP value was calculated as the ratio of the linear regression coefficient of the calibration curve for five dilutions of the sample and the linear regression coefficient of the FeSO 4 × 7 H 2 O standard curve [27]. Three independent determinations were performed for each sample.…”
Section: Determination Of the Antioxidant Capacitymentioning
confidence: 99%